2010
DOI: 10.1016/j.urology.2009.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Telomere DNA Content in Prostate Biopsies Predicts Early Rise in Prostate-specific Antigen After Radical Prostatectomy for Prostate Cancer

Abstract: Objective To determine whether measurement of telomere DNA content (TC) in prostate biopsy tissue predicts PSA recurrence in men after undergoing radical prostatectomy for prostate cancer. Methods Slot blot titration assay was used to quantitate TC in archived diagnostic prostate needle biopsy specimens for subjects (n=103) diagnosed with prostate cancer and who subsequently underwent radical prostatectomy between 1993 and 1997. TC was compared to the clinical outcome measure, PSA recurrence, defined as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…These findings are not in complete agreement with our previous study on telomere DNA content (TC), a proxy for telomere length and a marker of genomic instability, which we found to be reduced in histologically normal tissues adjacent to prostate adenocarcinomas, indicating field cancerization [10,11]. Of note, we used TC in biopsies to predict early rise in prostate specific antigen (PSA; biochemical recurrence) after prostatectomy [12]. A possible reason for this discrepancy, apart from sample size, is the higher inter- and intra-tissue heterogeneity (coefficients of variation up to 71% for the latter) determined for EGR-1 and FAS expression in all cohorts investigated herein.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These findings are not in complete agreement with our previous study on telomere DNA content (TC), a proxy for telomere length and a marker of genomic instability, which we found to be reduced in histologically normal tissues adjacent to prostate adenocarcinomas, indicating field cancerization [10,11]. Of note, we used TC in biopsies to predict early rise in prostate specific antigen (PSA; biochemical recurrence) after prostatectomy [12]. A possible reason for this discrepancy, apart from sample size, is the higher inter- and intra-tissue heterogeneity (coefficients of variation up to 71% for the latter) determined for EGR-1 and FAS expression in all cohorts investigated herein.…”
Section: Discussionmentioning
confidence: 56%
“…Reported aberrant expressional changes in field cancerized prostatic tissues include both RNA/cDNA and protein signatures identified by highly parallel technologies such as genomics and proteomics, as well as alterations of distinct proteins with different cellular function, including proliferation and anti-apoptosis (Ki67, Akt, androgen receptor), metabolism (alpha-methylacyl-CoA-racemase), and inflammation (cyclooxygenase 2) ([8,9] and references therein). Our own research into the molecular characterization of prostatic field cancerization has included genetic [1012] and RNA expressional [13] investigations. These studies have revealed the up-regulation of potential new indicators and/or mediators of field cancerization in prostate glands containing adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Most are a consequence of the natural aging process-age is the most significant risk factor for PCa development. In addition to the genetic causes already mentioned, factors that contribute to the carcinogenesis of PCa include inflammation (Gueron et al, 2012;Kazma et al, 2012;Sfanos and de Marzo, 2012), oxidative stress and DNA damage (Miyake et al, 2004;Lockett et al, 2006;Battisti et al, 2011;Gupta-Elera et al, 2012), telomere shortening and telomerase activity (Kageyama et al, 1997;Donaldson et al, 1999;Fordyce et al, 2005;Treat et al, 2010;Xu et al, 2011), genomic alterations (Boyd et al, 2012;Nyquist and Dehm, 2013), and epigenetic modifications (Okino et al, 2007;Goering et al, 2012). Efforts have been made to achieve a deep understanding of these factors and consequently improve diagnosis and management of patients.…”
Section: Underlying Prostate Cancer Development and Metastasis Formationmentioning
confidence: 99%
“…Even after adjustment for age, Gleason score and node No [68] Singh et al Yes, internally via software algorithm [78] Svensson et al Yes, but 7 out of 12 patients were misclassified [134] Valdagni et al status, diminished telomere DNA content was a significant predictor of BCR (HR: 5.02; p < 0.02). In a more recent study, the same group analyzed preoperative transrectal biopsy tissue from 103 men who went on to undergo RP [102]. In the overall cohort, low telomere DNA content was not a significant predictor of BCR on multivariate analysis.…”
Section: Reviewmentioning
confidence: 99%